How do you differentiate f(x) = (x^2-4x)/(xcotx+1) using the quotient rule? Calculus Basic Differentiation Rules Quotient Rule 1 Answer Καδήρ Κ. Jul 21, 2017 (df)/dx=((2x-4)(xcotx+1)+(x/sin^2theta-cotx)(x^2-4x))/(xcotx+1)^2 Explanation: (df)/dx=((d(x^2-4x))/dx(xcotx+1)-(d(xcotx+1))/dx(x^2-4x))/(xcotx+1)^2= ((2x-4)(xcotx+1)-(-x/sin^2theta+cotx)(x^2-4x))/(xcotx+1)^2= ((2x-4)(xcotx+1)+(x/sin^2theta-cotx)(x^2-4x))/(xcotx+1)^2 Answer link Related questions What is the Quotient Rule for derivatives? How do I use the quotient rule to find the derivative? How do you prove the quotient rule? How do you use the quotient rule to differentiate y=(2x^4-3x)/(4x-1)? How do you use the quotient rule to differentiate y=cos(x)/ln(x)? How do you use the quotient rule to find the derivative of y=tan(x) ? How do you use the quotient rule to find the derivative of y=x/(x^2+1) ? How do you use the quotient rule to find the derivative of y=(e^x+1)/(e^x-1) ? How do you use the quotient rule to find the derivative of y=(x-sqrt(x))/(x^(1/3)) ? How do you use the quotient rule to find the derivative of y=x/(3+e^x) ? See all questions in Quotient Rule Impact of this question 1630 views around the world You can reuse this answer Creative Commons License